Researching Young Children’s Lived Experiences of Loneliness: Pedagogical Implications for Linguistically Diverse Students - Kirova-Petrova, Anna (Alberta Journal of Educational Research, 2000)
This article addresses the pedagogical implications of linguistically diverse students' experiences of loneliness in elementary school. The study presented was derived from a larger investigation of young children's lived experiences of loneliness. A review of interviews with 10 linguistically diverse students in the original study revealed that these children experience the loneliness of being excluded, unwanted, and disliked, as well as empty of happiness, as a result of their inability to communicate appropriately with their peers. The students' loss of self-esteem and sense of self-worth and the development of learned helplessness syndrome are directly related to the persistence of their experiences of loneliness over a long period. Providing opportunities for meaningful social interactions in activities that do not require the English language as a sole means of expression of their knowledge and skills and teachers' effective use of nonverbal communication can be employed as strategies to foster a sense of belonging to the peer group and to promote hopefulness, which can lead to a reduction of feelings of loneliness in young linguistically diverse children.